2013
DOI: 10.1097/iae.0b013e318260246f
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associations of Retinal Vein Occlusions

Abstract: In the rural agrarian low-income population of Central India, RVOs were detected in 0.8% of adults, with branch retinal vein occlusions being approximately seven times more common than central retinal vein occlusions. Main associated factors were higher age, blood pressure, urea blood concentration, and narrow chamber angle. RVOs were no major reason for visual impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
2
35
1
3
Order By: Relevance
“…2,9,12,28 In our study group, about 10% patients had ocular hypertension which is not significant with actual 90% CI and considered it not to be a risk factor. 3,9,11,12 In our study group in 40% shorter axial length was found with a mean axial length of 22.41 mm. 29 Various studies have suggested that eyes with shorter axial length have a smaller disc and a narrower sclera canal, hence retinal vessels are enclosed within a limited space.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…2,9,12,28 In our study group, about 10% patients had ocular hypertension which is not significant with actual 90% CI and considered it not to be a risk factor. 3,9,11,12 In our study group in 40% shorter axial length was found with a mean axial length of 22.41 mm. 29 Various studies have suggested that eyes with shorter axial length have a smaller disc and a narrower sclera canal, hence retinal vessels are enclosed within a limited space.…”
Section: Discussionmentioning
confidence: 79%
“…These findings are in conformity with study done by many authors. 3,5,9,[16][17][18][19] In our study we noted that out of 100 patients 80 were males (80%) and 20 (20%) were female patients. Our study on BRVO showed male preponderance which is in concordance with the study done by Jhonson et al, Rath et al as they reported higher rates in males.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study conducted in central India, RVOs were detected in 0.8% of the adults examined, with branch vein occlusions being approximately seven times more common than central vein occlusions [2].There are two variants: non-ischemic and ischemic [3]. The causes for visual loss are macular edema and ischemia.…”
Section: Introductionmentioning
confidence: 99%